Reconstructing Islamic Education Management through Prophetic Leadership and Sufism in Educational Institutions - Fadhilah Hanjani Putri; Ahmad Barizi; Nur Ismiyahyi; Fifin Novi Saputri (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the integration of prophetic leadership and Sufism as a foundation for reconstructing Islamic education management in educational institutions. The research employs a qualitative method with a library research approach through the examination of various relevant literature on Islamic education management, prophetic leadership, and Sufism. The findings indicate that the reconstruction of Islamic education management can be developed through four main dimensions: prophetic planning based on prophetic values, shura-based organizing that emphasizes participation and consultation, prophetic leadership that implements the principles of siddiq (truthfulness), amanah (trustworthiness), tabligh (effective communication), and fathanah (wisdom and intelligence), as well as muraqabah-based supervision that integrates organizational control with spiritual consciousness. The integration of prophetic leadership and Sufism contributes to the development of a management system that is organizationally effective while fostering spiritual awareness, social ethics, and moral transformation. The novelty of this study lies in the formulation of a reconstructed Islamic education management model that integrates the principles of prophetic leadership with Sufi values as a management framework capable of adapting to contemporary educational challenges without neglecting the spiritual dimensions of Islam.